Cross‐Saharan transport of water vapor via recycled cold pool outflows from moist convection. Issue 3 (4th February 2017) - Trzeciak, Tomasz M.; Garcia‐Carreras, Luis; Marsham, John H.
Abstract: Very sparse data have previously limited observational studies of meteorological processes in the Sahara. We present an observed case of convectively driven water vapor transport crossing the Sahara over 2.5 days in June 2012, from the Sahel in the south to the Atlas in the north. A daily cycle is observed, with deep convection in the evening generating moist cold pools that fed the next day's convection; the convection then generated new cold pools, providing a vertical recycling of moisture. Trajectories driven by analyses were able to capture the direction of the transport but not its full extent, particularly at night when cold pools are most active, and analyses missed much of the water content of cold pools. The results highlight the importance of cold pools for moisture transport, dust and clouds, and demonstrate the need to include these processes in models in order to improve the representation of Saharan atmosphere. Key Points: Observed case of convectively driven water vapor transport across the Sahara over 2.5 days Cycle of convection generating cold pools which feed next day's convection, enhancing transport Analyses capture direction of transport but not its full extent due to missing cold pools